Efektivitas Model Pembelajaran Contextual Teaching and Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Sara Serlina Aulia; Hermansah (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
This research aims to determine the effectiveness of the contextual teaching and learning model on students' mathematical problem-solving abilities. This type of research is quasi experimental research with a pre-test post-test control group design. The population in this study were all class VIII students at the Wustho An-Ni'mah Batam Salafiyah Islamic Boarding School. The subjects in this research were 22 students from class VIII A as the experimental class and 12 students from class VIII B as the control class. The sampling technique was carried out using a saturated sample technique. Data was obtained with a test instrument consisting of 4 questions which had been tested for validity and reliability (rii = 0.67). The data analysis techniques used are normality tests, homogeneity tests, and hypothesis tests which include paired sample t-test and independent sample t-test. Based on the results of data analysis, (1) The CTL learning model is effective on students' mathematical problem-solving abilities, (2) The Direct Instruction learning model is not effective for students' mathematical problem-solving abilities, (3) There are differences in the effectiveness of the CTL learning model and the Direct Instruction learning model on students' mathematical problem solving abilities.